Magnetic field influence on the sedimentation of cells containing magnetic particles. - N. N. Komova; T. A. Nikolskaya (Тонкие химические технологии, 2009)
Magnetic field influence on the macrophage with the absorbed magnetic particles is investigated. It is demonstrated that the application of magnetic field changes the speed of sedimentation of cells. Changes of the nonsymmetrical indicatrix of the scattered light indicates that shape of the cells have changed under the influence of the magnetic field.